Battery wastewater induces nephrotoxicity via disordering the mitochondrial dynamics. (September 2022) - Yi, Jiangnan; Liao, Jianzhao; Bai, Tian; Wang, Bole; Yangzom, Chamba; Ahmed, Zulfiqar; Mehmood, Khalid; Abbas, Rao Zahid; Li, Ying; Tang, Zhaoxin; Zhang, Hui
Abstract: The rapid development of new energy battery enterprises manifolds the obsolete and scrapped batteries which are considered serious concern for the environment and ecology. Increasing trend of recycling batteries waste is public hazard throughout the world. The batteries wastes affect the various body systems but exact toxicological mechanism of battery wastewater is still unexplored. The present study was designed to observe the toxicological effects of batteries wastes on kidney functional dynamics. In this experiment, a total of 20 male mice were randomly divided into two groups including control and treatment (battery wastewater) group. The control group was provided the normal saline while the battery wastewater group were provided battery waste-water for a period of 21 days. The isolated kidneys were processed for histopathological analysis, biochemical assays, mRNA and protein estimation. The results showed that battery wastewater provision increased the mitochondrial division-related genes and proteins (Drp1, MFF, Fis1) and decreased the expression level of fusion-related nuclear proteins (MFN1, MFN2, OPA1) in kidneys. Moreover, the battery wastewater exposure significantly up-regulated the autophagy (PINK, Parkin, mTOR, ATG5, LC3-b, p62) and apoptosis (Bax, Cytc, APAF1, P53, Caspase3, Caspase8) related mRNA and proteins levels in kidneys. However, down-regulation of mRNA and proteins levels of Bcl2 and Beclin1 were also observed in kidneys after batteries wastes exposure. In conclusion, it is evident that the battery wastewater leads to renal apoptosis and autophagy by disrupting the mitochondrial dynamics in mice kidneys. Graphical abstract: Image 1 Highlights: Battery wastewater exposure damages kidney deconstruction and induces renal inflammation. Battery wastewater exposure induces kidney mitochondrial-mediated apoptosis. The disorder of mitochondrial dynamics promotes apoptosis. Battery wastewater exposure induces nephrotoxicity via elevating autophagy.